Method of product placement in computer games. Qualitative research amongst Polish players - Magdalena Hofman-Kohlmeyer (Journal of Marketing and Consumer Behaviour in Emerging Markets)
Nowadays, new technologies enable practitioners to create brand experience in the virtual world of computer games. Marketers use product placement to reach potential and current customers. In the meantime, computer games have become an attractive medium because they attract an increasingly wider audience of different genders and various age groups. Therefore, an important issue is to know and systematize current methods of brand placement in computer games. For the purpose, the author carried out 20 in-depth interviews with players of chosen computer games, Second Life, Euro Truck Simulator 2 and The Sims. According to the analysis, it can be distinguished by the following typology: place of brand placement (before logging, inside the game, in separate windows, and on external websites), brand availability (paid brand appearance and free brand appearance), the source of brand placement (game producer, organizations, and players), virtual forms of promotion (advertising, public relations, direct marketing, personal selling, sales promotion, and word-of-mouth marketing), the degree of use of the branded product in game (full use and limited use of the branded product). The presented paper contributes to the theory of marketing communication and branding.